2021
DOI: 10.1002/smtd.202100900
|View full text |Cite
|
Sign up to set email alerts
|

Epidermis‐Inspired Wearable Piezoresistive Pressure Sensors Using Reduced Graphene Oxide Self‐Wrapped Copper Nanowire Networks

Abstract: Wearable piezoresistive sensors are being developed as electronic skins (E‐skin) for broad applications in human physiological monitoring and soft robotics. Tactile sensors with sufficient sensitivities, durability, and large dynamic ranges are required to replicate this critical component of the somatosensory system. Multiple micro/nanostructures, materials, and sensing modalities have been reported to address this need. However, a trade‐off arises between device performance and device complexity. Inspired by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…The parahydrophobic glove can be used for preparing a small amount of solution for experiments that are low cost and environmentally friendly. Such droplet-based microextractors and microreactors have broad application prospects in protein crystallization, enzyme kinetics, and other biochemical reactions. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parahydrophobic glove can be used for preparing a small amount of solution for experiments that are low cost and environmentally friendly. Such droplet-based microextractors and microreactors have broad application prospects in protein crystallization, enzyme kinetics, and other biochemical reactions. …”
Section: Resultsmentioning
confidence: 99%
“…These works mainly discuss the surface properties of textiles. So far, many efforts have been made to develop artificial bionic hydrophobic micropatterns with hierarchical structures on textiles, including coating, , etching, , chemical vapor deposition, , layer-by-layer self-assembly, etc. However, some complex hydrophobic patterns in nature exceed the ability of traditional manufacturing strategies, , resulting in the inability to accurately manufacture controllable nanostructures on textiles, which hinder the development of parahydrophobic textiles.…”
Section: Introductionmentioning
confidence: 99%
“…MNW networks are intrinsically stretchable due to strain dissipation of their porous structure. 384 Therefore, MNW-based conductors can be used as SEs for stretchable optoelectronics, including stretchable displays, 244 piezoresistive sensors, 385 wearable heaters, 386 epidermal electronics, 387 etc. An important parameter of SEs is stretchability which strongly depends on the morphologies of MNW networks.…”
Section: Applicationsmentioning
confidence: 99%
“…Previous reports have demonstrated that CL biosensors can noninvasively monitor pH, ions, and biomolecules with high precision and good efficiency in tears. [32][33][34][35][36][37][38][39] Previous CL biosensors were reported as a diagnostic tool for various ocular diseases. [24,40,41] Among the diverse materials used to fabricate CLs, poly(2-hydroxyethyl methacrylate)(PHEMA) has been adopted as a CL material due to its superb mechanical property, excellent optical clarity, and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%